Efektivitas Metode Tanya Jawab dalam Meningkatkan Pemahaman Materi PAI di Madrasah Aliyah Muhammadiyah 1 Medan - Afifah Hanum Lubis; Rizka Harfiani (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to determine the effectiveness of the question-and-answer method in improving students’ understanding of Islamic Education (PAI) material at Madrasah Aliyah Muhammadiyah 1 Medan. This research employs a quantitative approach with a simple descriptive design. The sample consisted of 5 respondents who were eleventh-grade students. The instruments used were comprehension tests administered before and after the implementation of the question-and-answer method, as well as observation sheets to assess student engagement during the learning process. The data were analyzed using mean and percentage calculations to identify the improvement in learning outcomes. The results show a significant increase in students’ understanding after applying the question-and-answer method. Students became more active in answering and asking questions, making the classroom atmosphere more interactive. This proves that the question-and-answer method is effective as a learning strategy in PAI to enhance students’ conceptual understanding. This study is expected to serve as a reference for PAI teachers in selecting appropriate teaching methods to improve the quality of the teaching and learning process.